Entrepreneurship and local economic development - Walzer, Norman (Lexington Books, 2007)
Entrepreneurship and Local Economic Development delves into the current thinking on local entrepreneurship development programs and evaluates ways in which practitioners can implement successful entrepreneurship practices. Examining the role and potential for entrepreneurship programs in local economic development strategies, contributors to this edited collection have many years of experience working with entrerpreneurship initiatives in state and local governments. Focused on theory and case study, Entrepreneurship and Local Economic Development examines conceptual issues involved in creatin.